2019
DOI: 10.1038/s41598-019-48530-5
|View full text |Cite
|
Sign up to set email alerts
|

Tree-ring correlations suggest links between moderate earthquakes and distant rockfalls in the Patagonian Cordillera

Abstract: Earthquakes with magnitudes M > 7 can trigger large landslides and rockfalls at epicenter distances of up to 400 km, whereas moderate shaking ( M = 5–7) is generally thought to result in abundant co-seismic mass movements in the vicinity of the epicenter. Although one might anticipate that large magnitude earthquakes off the Chilean coast would result in abundant rockfall in the Patagonian Cordillera, only limited research has explored this hypothesis. Here, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Mainieri et al [84] reported that abrupt growth suppression was the least common response of rockfall growth injuries. Stoffel et al [85] concluded that after rockfall injuries, 13% of the studied coniferous trees experienced strong growth after the injuries and that suppressed growth due to reduced vitality or photosynthesis was rare (only in 4% of cases). Since trees can react differently after wounding and considering that no branches or tree tops were affected at the Jelovica site, we presume that this is the reason why no differences between the injured and uninjured trees were present as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Mainieri et al [84] reported that abrupt growth suppression was the least common response of rockfall growth injuries. Stoffel et al [85] concluded that after rockfall injuries, 13% of the studied coniferous trees experienced strong growth after the injuries and that suppressed growth due to reduced vitality or photosynthesis was rare (only in 4% of cases). Since trees can react differently after wounding and considering that no branches or tree tops were affected at the Jelovica site, we presume that this is the reason why no differences between the injured and uninjured trees were present as yet.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, such events might facilitate the growth of trees by reducing neighborhood competition (Kitzberger et al., 1995), supplying sufficient soil nutrients and moisture (Bekker et al., 2018; Cheng et al., 2012) or enhancing photosynthesis (Mohr et al., 2021). Hence, variations in annual growth in trees (tree‐ring width data) are often used to date earthquake events and thus, are considered as one of the potential proxies in understanding earthquakes' impacts on forests (Pedrera et al., 2014; Stoffel et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The Andean mountains, the longest mountain chain of the world and the second highest, is periodically affected by large magnitude earthquakes. Resulting ground motions can trigger several adverse events such as landslides and floods, and are considered as one of the main drivers of local rockfall activity (Stoffel et al., 2019). Losses directly related to earthquake hazard (e.g., collapse of buildings and failure of infrastructures) are increasingly well understood and quantified.…”
Section: Introductionmentioning
confidence: 99%